2022
DOI: 10.1177/09636897221109884
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With Vitamin E, Zinc, Selenium, and Copper Re-Establishes T-Cell Function and Improves Motor Recovery in a Rat Model of Spinal Cord Injury

Abstract: Spinal cord injury (SCI) causes a dysfunction of sympathetic nervous system innervation that affects the immune system, leading to immunosuppression syndrome (ISS) and contributing to patient degeneration and increased risk of several infections. A possible therapeutic strategy that could avoid further patient deterioration is the supplementation with Vitamin E or trace elements, such as Zinc, Selenium, and Copper, which individually promotes T-cell differentiation and proliferative responses. For this reason,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Many studies have confirmed that copper plays a vital role in the function of the mammalian immune system; for example, animals with copper deficiency are more vulnerable to infections, whereas animals that consume an oral diet that is rich in copper are more resistant [ 57 ]; oral copper supplementation helps to maintain T-cell function in rats with acute spinal cord injury [ 58 ]. From the perspective of the immune system, the body needs balanced copper intake; moderate copper intake is sufficient for optimal immune function, while too much may be harmful to the organism [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that copper plays a vital role in the function of the mammalian immune system; for example, animals with copper deficiency are more vulnerable to infections, whereas animals that consume an oral diet that is rich in copper are more resistant [ 57 ]; oral copper supplementation helps to maintain T-cell function in rats with acute spinal cord injury [ 58 ]. From the perspective of the immune system, the body needs balanced copper intake; moderate copper intake is sufficient for optimal immune function, while too much may be harmful to the organism [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have con rmed that copper plays a vital role in the function of the mammalian immune system; for example, animals with copper de ciency are more vulnerable to infections, whereas animals that consume an oral diet that is rich in copper are more resistant [38]; oral copper supplementation helps to maintain T-cell function in rats with acute spinal cord injury [39]. From the perspective of the immune system, the body needs balanced copper intake; moderate copper intake is su cient for optimal immune function, while too much may be harmful to the organism [40].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with trace elements and vitamin E maintains the number and function of T-lymphocytes after acute SCI. This therapeutic strategy also promotes motor recovery, which is probably due to its antioxidant effect [ 159 ].…”
Section: Supplements and Probiotics As Therapeutic Strategies After S...mentioning
confidence: 99%